Investigation of soil property changes and olive tree stress as caused by excessive sewage-sludge application - Tsadila, E.; Tsadilas, C.; Stamatiadis, S.; Christodoulakis, N. (Communications in Soil Science and Plant Analysis, 2009)
This study was undertaken to assess the impact of a single excessive sludge application (300 Mg ha-1) on the soil surface of an olive orchard several years after the event. Selected soil properties were compared in two soil profiles, one in the sludge-amended field and another in an adjacent unamended field of naturally growing trees. Leaf analysis included macronutrients [nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg)], trace elements [copper (Cu), zinc (Zn), manganese (Mn), iron (Fe), nickel (Ni), boron (B)], and isotopic composition (δ 15N and δ 13C). Soil pH and other chemical properties were increased in the surface soil and the root zone of the sludge-treated profile in comparison to those of the untreated control. The multifold increase of Bray P and nitrates indicated a serious risk for dissolved phosphates in runoff and nitrate contamination of groundwater. Trace-element content also increased, but not greater than the critical soil concentration. Olive trees responded to excessive sludge application by increased N uptake as evidenced by increased leaf N content and elevated 15N signal. The increased leaf δ 13C signal of the leaves further indicated tree stress in the sludge-amended field during the summer growing season in comparison to the naturally growing control trees. Isotopic composition, leaf nutrient, and trace element concentration did not reveal the causes of leaf tip burning in half of the trees of the sludge-amended field. Copyright © Taylor & Francis Group, LLC.
Keywords: environmental stress; evergreen tree; Groundwater pollution; heavy metal; Heavy metal fractionation; isotopic composition; nutrient uptake; Olive tree; orchard; pH; Sewage sludge; sludge; soil amendment; soil nutrient; soil profile; soil property; Soil remediation; soil surface; trace element